Aetiology of students’ violent behaviour: the case of an urban school in Zimbabwe - Gudyanga, Ephias; Gudyanga, Anna; Matamba, Nomsa (Global Institute for Research and Education, 2019)
The study is premised on the aetiology (causes) of violent behaviour in a purposively selected urban secondary school in Gweru - Zimbabwe. The visual participatory methodology was used, whereby drawings and focus group discussions were the methods used to generate data over a period of two weeks. Participants were fifteen conveniently selected students attending a typical high density urban secondary school (females = 7, age range 15-17, males = 8, age range 14-18). Findings showed that the majority of the students exhibited violent behaviour as a result of their family backgrounds, neighbourhood set-up, school environment and personal attitudes. Some prominent causal factors included high incidences of violence in the community where students live, parents’ misunderstandings and fighting at home, shortage of school furniture, harsh parental discipline and overwhelming schoolwork. Violence among students in the selected urban secondary school requires urgent proactive policies, where stakeholders, including school authorities, parents, students and community engagement are incorporated in an endeavour to reduce or eliminate violence at school.